On Order of Banach Valued Analytic Functions (Journal of Informatics and Mathematical Sciences, 2012)
We consider Banach valued analytic functions and show that the order of a Banach valued analytic function is the same as that of its derivative.
Keywords: Banach valued functions; Analytic functions; Order; Derivative